Efeitos da prática mental na aquisição de habilidades motoras em sujeitos novato: eficaz, insuficiente ou inexistente? - Thabata Viviane Brandao Gomes (2009)
he contribution of mental practice in motor skill acquisition in naive subjects is still not clear. Mental practice is more effective than absence of practice but mental practice alone is not as effective as physical practice and combination of physical and mental practice (combined practice). Some studies with naive showed that mental practice was better than no practice (control group); however, experimental designused some kind of physical practice as task familiarization or pre-test. Following this way of thinking, maybe physical practice presents in combined practice is just enough to learning the task. Thus, this study aimed to investigate the effects of mental practice in naive motor skill learning. Sixty university students practiced a serial aiming task with a sequence and target time established. The sample was distributed in five groups (n=12): MPG (mental practice group), PPG (physical practice group), MPPG (mental-physical practice group), PMPG (physical-mentalpractice group), and CG (control group). The experiment was divided in three phases: acquisition, retention test, and transfer test. In the acquisition phase and retention test, the task was to transport three tennis balls with non-preferred hand, in 5-1/4-5/6-4 sequence and target time of 3,500 ms. and, in the transfer test, in 5-3/6- 5/4-6 sequence and target time of 4,500 ms. Except CG, that participated only intests, all groups practiced 6 trials in acquisition phase, being PPG realized 6 trials of physical practice, MPG realized 6 trials of mental practice, PMPG realized 3 trials of physical practice in the beginning and after them, 3 trials of mental practice and the MPPG practiced on the inverted order. A Mann-Whitney (between groups) and Wilconxon (within group) tests were used to data analysis in acquisition phase. AKruskal-Wallis test was used in retention and transfer tests. It was used a 5% to alpha risk (level of significance of p<0.05) for these tests. The Mann-Whitney posthoc test using the Bonferroni procedure to adjust the level of significance as well (p<0.005). In physical practice trials of acquisition phase, PPG and PMPG were similar and PPG had better performance than MPPG. Tests results showed better performance of PPG upon MPG and CG, and better performance of MPPG uponMPG. The results suggest that physical practice is fundamental, and mental practice does not contribute to naive motor skill acquisition. Mental practice was considered insufficient, because only mental practice does not provide learning. But, it was efficient in combined practice, especially when it was positioned before physical practice.